Patient-reported outcomes in individuals with hepatitis C virus infection treated with elbasvir/grazoprevir - Ng, Xinyi; Nwankwo, Chizoba; Arduino, Jean Marie; Corman, Shelby; Lasch, Kathryn Eilene; Lustrino, Jacqueline Mary; Patel, Sushma; Platt, Heather Loryn; Qiu, Jingjun; Sperl, Jan (Patient preference and adherence, 2018)
PURPOSE: People chronically infected with hepatitis C virus (HCV) have diminished patient-reported outcomes (PROs). This study aimed to compare the impact of elbasvir/grazoprevir (EBR/GZR) treatment versus sofosbuvir with pegylated interferon and ribavirin (SOF/PR) on changes in PROs: 1) during the treatment period and 2) at posttreatment follow-up. PATIENTS AND METHODS: PRO data collected during the Phase III C-EDGE Head-2-Head (H2H) open-label study was analyzed. In this trial, patients infected with HCV were randomized 1:1 to receive either EBR/GZR or SOF/PR for 12 weeks. Patients self-administered the Short Form-36 version 2 (SF-36v2®) Health Survey Acute (1-week recall) Form and the Functional Assessment of Chronic Illness Therapy-Fatigue (FACIT-Fatigue) Scale at baseline, during treatment, and posttreatment. Between-group differences in mean change of PRO scores from baseline were estimated during the treatment period and also at the posttreatment follow-up. Effect sizes were calculated to evaluate if the detected change in mean PRO scores is clinically meaningful between groups. RESULTS: There were 255 patients (99.2% White, 54.1% female, 74.9% treatment naïve) included in the analysis. During the treatment period, significant declines in SF-36v2 scores were observed across all domains for the SOF/PR group. Compared to the SOF/PR group, the EBR/GZR group reported more improvement in scores across all SF-36v2 domain scores at the end of the treatment period. At treatment week 12, the between-group differences for 6 out of the 8 domain scores for these patients reflected at least moderate effects (effect sizes >0.5). No significant between-group differences in change in SF-36v2 scores from baseline were detected posttreatment. The decline in SF-36v2 scores observed during the treatment period for the SOF/PR group returned to near baseline scores or above posttreatment. Treatment with EBR/GZR did not impact fatigue scores, but treatment with SOF/PR led to increased fatigue scores during treatment which resolved by posttreatment follow-up week 12. CONCLUSION: This study demonstrated that HCV treatment with EBR/GZR resulted in a significantly better PRO profile as compared to SOF/PR. PROs are an important consideration as worsening PROs experienced during treatment may negatively influence adherence and ultimately contribute to an unfavorable clinical outcome. CLINICALTRIALSGOV IDENTIFIER: NCT02358044.
Keywords: hepatitis; patient-reported outcomes; fatigue; health-related quality of life; direct-acting antivirals